The EU-Brazil partnership and the new climate geopolitics: Strategically reconciling decarbonisation and competition - Jule Könneke (Stiftung Wissenschaft und Politik (SWP), 2024)
The new EU Commission is promising to improve the bloc's geoeconomic resilience, make progress on decarbonisation and increase competitiveness. Achieving these aims will mean working with emerging economies like Brazil - where the EU's influence is waning as China's expands. The EU lacks a long-term strategy and is poorly positioned to engage with a newly assertive Brazil in an increasingly multipolar world. This is increasingly problematic for the EU's strategic agenda.
Keywords: 320; EU Commission; European Green Deal (EGD); EU Regulation on Deforestation-free Products (EUDR); EU's strategic agenda; greenhouse gases; geoeconomic resilience; decarbonisation; competitiveness; green technology; Donald Trump; Clean Industrial Deal; Net Zero Industry Act; Critical Raw Materials Act; Mercosur; Brazil; Luiz Inácio Lula da Silva; Carbon Border Adjustment Mechanism (CBAM); BRICS; Belt and Road Initiative (BRI)